Islamic Work Ethic of Employees of PT. Asuransi Jiwa Manulife Indonesia (Manulife Indonesia) Branch Office of Bank Danamon Indonesia, Tbk Mataram City - Hulaimi, Ahmad; Hidayanti, Nur Fitri (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The religion of Islam which is based on the Qur’an and al-Hadith as a guide and guidance for Muslims has a function not only to regulate in terms of worship but also to regulate the people in making demands in matters relating to work. In the Qur’an and al-Hadith, it is clear about good work and how we earn sustenance in a way that pleases Allah SWT. It is very important to discuss this, the work ethic in the Islamic view is the knitting of values ​​that shape the personality of a Muslim at work. Many of us encounter in print and electronic media, customers who complain about the service or type of satisfaction provided by the company. This study aims to determine the extent of the process from start to finish in ensuring the company PT. Asuransi Jiwa Manulife Indonesia (Manulife Indonesia) Branch Office of Bank Danamon Indonesia, Tbk Kota Mataram, so that the information obtained can help the wider community, especially the Indonesian people. This study used a qualitative approach and observations were conducted from January 2023 to February 2023. Data collection techniques were carried out by means of 1) Observation 2) Interviews, and 3) Documentation, as well as technical analysis of the data obtained by the researchers, both the results of interviews with several informants, observations, and documentation that were later processed by researchers and analyzed qualitatively. The results of the research, it has been found in the field that marketing department employees have been dishonest to prospective customers. In the future, there will be inconvenience to customers which results in customer distrust of the company. Therefore, the work ethic in Islam is not enough to only rely on conceptual abilities, but also on high moral commitment and noble character. The Qur’an says that “Allah made human beings a caliph for common prosperity that is carried out fairly and does not follow lust.” The religion of Islam which is based on the Qur’an and al-Hadith as a guide and guidance for Muslims has a function not only to regulate in terms of worship but also to regulate the people in making demands in matters relating to work. In the Qur’an and al-Hadith, it is clear about good work and how we earn sustenance in a way that pleases Allah SWT. It is very important to discuss this, the work ethic in the Islamic view is the knitting of values ​​that shape the personality of a Muslim at work. Many of us encounter in print and electronic media, customers who complain about the service or type of satisfaction provided by the company. This study aims to determine the extent of the process from start to finish in ensuring the company PT. Asuransi Jiwa Manulife Indonesia (Manulife Indonesia) Branch Office of Bank Danamon Indonesia, Tbk Kota Mataram, so that the information obtained can help the wider community, especially the Indonesian people. This study used a qualitative approach and observations were conducted from January 2023 to February 2023. Data collection techniques were carried out by means of 1) Observation 2) Interviews, and 3) Documentation, as well as technical analysis of the data obtained by the researchers, both the results of interviews with several informants, observations, and documentation that were later processed by researchers and analyzed qualitatively. The results of the research, it has been found in the field that marketing department employees have been dishonest to prospective customers. In the future, there will be inconvenience to customers which results in customer distrust of the company. Therefore, the work ethic in Islam is not enough to only rely on conceptual abilities, but also on high moral commitment and noble character. The Qur’an says that “Allah made human beings a caliph for common prosperity that is carried out fairly and does not follow lust.”